Methodology for Assessing Voltage–Reactive Power Capability of Synchronous Units under Modified Transformer Impedance - Mijajlovic, Anita; Dragosavac, Jasna; Janda, Žarko; Klasnić, Ilija (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
This paper presents a methodology for evaluating the voltage–reactive power capability of synchronous generators following changes in transformer impedance. The framework integrates per-unit calculations, an equivalent generator–transformer model, and numerical simulations across multiple grid-voltage scenarios. The SIM-Operating Map application provides analytical and graphical verification of reactive margins, limiting factors, and grid-code compliance, supporting operational decision-making and enhancing system security after transformer replacement.
Keywords: reactive capability; transformer impedance; per-unit modeling; SIM-Operating Map